Drop-out model optimization on degraded DNA samples. (December 2015) - Duchamp, V.; Bastisch, I.; Schneider, P.M.
Abstract: Two statistical models have been developed to interpret locus drop-out resulting from degraded DNA samples. These models are based on an experimental dataset of 600 genotyping experiments. The first model presents the probability of locus drop-out against the average peak height with a lower and upper confidence interval. For a given peak height average, the probability of drop-out can be quite wide. This probability decreases rapidly when the profile quality increases. For the second model, we have fitted the probability of locus drop-out against the number of base pairs with a lower and upper confidence interval. The probability of drop-out is increasing along with the number of base pairs. Despite DNA degradation effects, the drop-out probability does not get higher than 0.5.